MAKEBELIEFSCOMIX.COM WEB TRAINING TO CREATE FUN-LEARNING MEDIA IN KB-RA MUSLIMAT SURABAYA: PELATIHAN PEMBUATAN MEDIA PEMBELAJARAN MENGGUNAKAN WEB MAKEBELIEFSCOMIX.COM DI KB-RA MUSLIMAT SURABAYA - Elda Yulia Ryandini; Chowal Jundy Kumoro; Felicia Yohanna Restiarti Ponga (Darmabakti Cendekia: Journal of Community Service and Engagements, 2024)
Background: Learning media is a component which takes place in the learning process for the education level. With the development of sophisticated technology, everyone in the education field is demanded to be able to apply the use of digital technology media for the learning process because of the unseparated use of technology in education. Objective: This activity aims to give a short course about making cartoon learning media using the makebeliefscomix.com web for learning activities for KB-RA Muslimat students. Method: This activity was carried out at KB-RA Muslimat Surabaya for 2 days to 8 teachers. The team provided material and created learning media using makebeliefscomix.com web and continued with material about marketing used as a theme in making cartoons. Results: The difficulties in creating learning media are in operating laptops, signing up, using email, determining topics, and incompatibility of material topics. However, all participants were able to complete the media creation well and enthusiastically and stated that this media is useful. Conclusion: All teacher participants were able to follow the instructions well, use and create interesting dialogue on the topic of marketing a product using Makebeliefscomix media even though they experienced several obstacles at the beginning of production.